Mobile phones and children: exposure and pattern of usage of mobile phones among children - a descriptive cross-sectional study - Reddy, Duvvur Preethika; Earan, Sujay Kumar; Thambiprabagarane Kalaimani,; Arulkumaran Arunagirinathan, (International Journal of Contemporary Pediatrics, 2023)
Background: Mobile phone as an invention of the modern world has managed to penetrate not only the most distant parts of the world but also various age groups in a person’s life. There is a need to evaluate the children’ interactions with these modern devices as they might have a significant effect on their behavior, sleep patterns, and psychological addiction. Objectives of the research were: to study the socio demographic characteristics of children using mobile phones, to determine the average time duration of exposure to mobile phones, and to determine the age of initial exposure to mobile phones. Methods: It was a descriptive cross sectional observational study. The study was conducted at Sri Manakula Vinayagar Medical College and Hospital. All the children between the age group of 0-12 years visiting the pediatric outpatient department fulfilling the inclusion criteria were enrolled in the study. Results: Of the 248 children enrolled in the study mobile phone exposure was found in 143 (57.66%) boys and 105 (42.34%) girls. 67.74% of the parents agreed that the mobile phones were being used by their children just for fun without any intended or specific use. 26% of the times it was used to engage the children when the parents were busy. 30.24% of the kids had a screen time of less than 30 minutes on a daily basis. 23.39% of the children were used to the screen for more than 2 hours in a day, on a cumulative basis. It was noted that more than 50% of children were exposed to mobile phones within 1 year of age. The earliest age of exposure to mobile phone was 2 months of age. Conclusions: Regardless of the socioeconomic status the accessibility and the owning of the mobile phones is same across the socioeconomic strata. The need of the hour is to raise awareness among the parents regarding the excessive use of mobile phones among children and their possible adverse impacts on physical and psychosocial health.